A 4-Year Surveillance of Device-associated Nosocomial Infections in a Neonatal Intensive Care Unit - Recep Tekin; Tuba Dal; Habibe Pirinccioglu; Seyhan Erisir Oygucu (Pediatrics and Neonatology, 2013)
The aim of this study was to determine the rate of health care-associated infection (HC-AI) and device-associated health care-associated infections (DA-HAIs), and distribution of causative microorganisms and etiologic factors responsible for these infections in a neonatal intensive care unit (NICU) of a state hospital in southeastern Turkey. Methods: A laboratory-based, active, prospective nosocomial infection surveillance study was performed in NICUs from January 2008 to December 2011. The rates of HC-AIs were determined on a daily basis. The findings were evaluated by applying the definitions of the Centers for Disease Control and Prevention National Healthcare Safety Network. Results: In a 4-year period, 580 HC-AIs, 81 of which were DA-HAIs, were detected among 6932 patients. The rate of hospital acquired infection was 8.3% and 7.69/1000 patient days. Ventilator-associated pneumonia (VAP) was the second most frequent (13.1%) HC-AI and the most frequent was DA-HAI. The VAP rate was 6.4 per 1000 ventilator days. Mechanical ventilation was the most frequently used invasive device. Median time to diagnosis of VAP was 32.11 ± 29.3 days from the time of admission. Acinetobacter baumannii (48%) and Pseudomonas aeruginosa (32%) were the most frequent microorganisms. Colistin was the most effective antibiotic by in vitro test. The antibiotic resistance ratios of A. baumannii were ≥54% for carbapenems, aminoglycosides, and cefoperazone–sulbactam; ≥88% for quinolones; and ≥92% for ceftazidime, ceftriaxone, and piperacillin–tazobactam. Conclusions: Device-associated nosocomial infections was a particularly important problem in NICU. Close monitoring will decrease the rates of device-related nosocomial infections.